ISOFLURANE RESPIRATORY ANESTHETIC INDEX IN CHICKENS (GALLUS GALLUS DOMESTICUS) - Midon, Monica [UNESP]; Escobar, Andre [UNESP]; Yamada, Diego Iwao [UNESP]; Freitas, Pamela Oliveira de [UNESP]; Minto, Bruno Watanabe [UNESP]; Barletta, Michele (Amer Assoc Zoo Veterinarians, 2021)
Respiratory depression from isoflurane seems to be greater in birds than in mammals. Isoflurane respiratory anesthetic index (AI) has only been evaluated in ducks (Anas platyrhynchos), which indeed showed a lower AI compared to mammals, but the isoflurane AI for other avian species is not known. The aim of this study was to evaluate the isoflurane AI in chickens (Gallus gallus domesticus). Six adult hens were anesthetized with isoflurane for determination of the minimum anesthetic concentration (MAC) using the bracketing method. During a second anesthetic event, the isoflurane AI was determined by progressively increasing the expired fraction of isoflurane by 0.5 times MAC until apnea was achieved (ETiso-apnea). The isoflurane AI was considered the ratio between the ETiso-apnea and the MAC. Heart rate, systolic arterial pressure, respiratory rate, and end-tidal carbon dioxide were continuously monitored throughout both anesthetic events. Data were analyzed using a mixed-effect model with Greenhouse-Geisser correction, followed by Tukey's test. The MAC for isoflurane was 1.18% +/- 0.09% (mean +/- SD). The ETiso-apnea was 3.31% +/- 0.34% and the isoflurane AI was 2.80 +/- 0.26. In chickens, isoflurane AI is similar to that measured in mammals, which is in contrast with published data in other avian species.